Design of a new medical device for aiding clinical diagnosis of patellofemoral disorders - Leal, Ana (2015)
The purpose of the present work is, like the tittle says, to develop a system that could assist on the diagnosis of the patellofemoral disorders. Patellofemoral joint is one of the most complex articulations of the human body with high functional and biomechanical requirements. Anatomical and phys-iological abnormalities of this articulation result in knee problems with high social incidence and inten-sity. Therefore, their proper diagnosis and consequent correction might prevent or delay the development of diseases like arthrosis, decreasing their long-term negative impact in life-quality and health economy. Clinical history, physical examination and imaging studies should be complementary procedures in the diagnosis of patellofemoral disorders, but until now they cannot be performed simul-taneously. Furthermore, non-objectivity, inaccuracy and limited reliability and reproducibility are fre-quently found among the assessment methods. Since nowadays the majority of the cases of patello-femoral disorders are recurrently misdiagnosed, there is in fact an urgent need of standardization of the whole methodology. From idea conception to the design development, we believe this work may give a great contribution on these issues.